2007
DOI: 10.1007/s10517-007-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and antimetastatic activity of fucoidan, a sulfated polysaccharide isolated from the Okhotsk sea Fucus evanescens brown alga

Abstract: Antitumor and antimetastatic activities of fucoidan, a sulfated polysaccharide isolated from Fucus evanescens (brown alga in Okhotsk sea), was studied in C57Bl/6 mice with transplanted Lewis lung adenocarcinoma. Fucoidan after single and repeated administration in a dose of 10 mg/kg produced moderate antitumor and antimetastatic effects and potentiated the antimetastatic, but not antitumor activities of cyclophosphamide. Fucoidan in a dose of 25 mg/kg potentiated the toxic effect of cyclophosphamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(141 citation statements)
references
References 5 publications
2
136
0
3
Order By: Relevance
“…In fact, seaweeds are a great source of sulfated polysaccharides expressing anticoagulant, cytotoxic, antitumor, antimetastic activities (Alekseyenko et al, 2007;Li et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, seaweeds are a great source of sulfated polysaccharides expressing anticoagulant, cytotoxic, antitumor, antimetastic activities (Alekseyenko et al, 2007;Li et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al (1987) and Sheu et al (1996) reported that oral consumption of several seaweeds significantly decreased the incidence of carcinogenesis in vivo. Alekseyenko et al (2007) suggested that polysaccharide of Fucus evanescens has antitumor and antimetastatic activity in C57BI/6 mice with transplanted Lewis lung adenocarcinoma. Down-regulating tissue factor expression, Grateloupia longifolia polysaccharide inhibits angiogenesis in HMEC-1 endothelial cells (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan (10 mg/kg) alone possess moderate antitumor and antimetastatic effects. In addition, this fucoidan potentiates the antimetastatic but not antitumor activities of cyclophosphamide (drug used for chemotherapy) and, at 25 mg/kg, increases the toxic effect of cyclophosphamide (Alekseyenko et al, 2007).…”
Section: Anticancer Activitymentioning
confidence: 99%